2023
DOI: 10.3390/cancers15072045
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence in Korean Healthcare Workers in Hospitals

Abstract: Objectives: Healthcare workers in hospitals (HHCWs), a notably increasing workforce, face various occupational hazards. A high incidence of cancer among HHCWs has been observed; however, the cancer incidence status among HHCWs in South Korea is yet to be studied. This study aimed to assess cancer incidence among HHCWs in South Korea. Methods: We constructed a retrospective cohort of HHCWs using National Health Insurance claims data, including cancer incidence status and vital status, from 2007 to 2015. Those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“… 13 A study in Korea that used a nationwide health insurance database to construct a retrospective cohort of 107,646 female healthcare workers in hospitals revealed a significantly increased SIR for breast cancer compared to the entire worker population (SIR: 1.21, 95% CI: 1.09–1.36). 14 These results are congruent with our study findings, where the SIR for breast cancer in female workers in the nursing department as a whole was significantly higher at 1.65 (95% CI: 1.08–2.41).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“… 13 A study in Korea that used a nationwide health insurance database to construct a retrospective cohort of 107,646 female healthcare workers in hospitals revealed a significantly increased SIR for breast cancer compared to the entire worker population (SIR: 1.21, 95% CI: 1.09–1.36). 14 These results are congruent with our study findings, where the SIR for breast cancer in female workers in the nursing department as a whole was significantly higher at 1.65 (95% CI: 1.08–2.41).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have revealed higher breast cancer incidence and mortality rates among nurses in South Korea as a whole. 14 26 However, this study indirectly confirmed the risk of some occupational hazards (antineoplastic drugs, job strain, and night shift work) for breast cancer by understanding the characteristics of the affiliated workplaces and tasks within a single large tertiary hospital based on internal personnel data.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations